Pesantren development strategy in the globalization era at the Ma'ruful Hidayah Foundation, Cigedug District, Garut Regency - Wawan Ridwan; Hasan Basri; Andewi Suhartini (ARKA INSTITUTE, 2022)
This study aims to identify and analyze external factors that can trigger opportunities and threats, as well as internal factors that describe strengths and weaknesses in Islamic boarding schools, so that appropriate strategies can be found to be applied to pesantren in improving their existence as an educational institution. Islam in environmental conditions that have turned into modern boarding schools. The focus of this research is the strategy of developing Islamic boarding schools in an effort to maintain their existence as an Islamic educational institution in the era of globalization. The type of research is qualitative research. The data analysis methods used are: Qualitative analysis, which is a series of activities to analyze data in the research object which is not stated in numbers but uses SWOT analysis. The results of the study indicate that the appropriate development strategies to be applied to Islamic boarding schools in the Cigedug sub-district, Garut Regency include; 1) there are 2 strategies for developing Islamic educational institutions, namely: adaptive and consistent, 2) pesantren management reform strategies, namely the application of professional management, 3) strategies for increasing resources in pesantren, namely: increasing Human Resources and Natural Resources.